Impact Of Online Transformation In Yogyakarta: PT Gojek Indonesia Through The Concept Of SDG Approach - Aris Munandar; David Efendi; Alam Mahadika (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2021)
Transportation is one of the basic human needs today, especially for the people of Yogyakarta city. The type of transportation that is most in – demand and is seen as providing significant benefits is Gojek online transportation. The existence of Gojek in the city of Yogyakarta has an impact on community. This research aims to look at these impacts by using the concept of sustainable development goals with environmental, social, economic pillars. Based in the research conducted, it was obtain that the existence of Gojek in the city of Yogyakarta has an environmental, social and economic impact. On environmental impact found that Gojek is one of the sustainable transportation. Researchers found that the volume of vehicles that have a lot of impact on congestion makes Yogyakarta the 4th most expensive city Indonesia but does not significantly impact air pollution. Gojek has succeeded in creating one rule that makes the distribution of pollution relatively stable. In addition to the policy factors of Gojek, the role of the Yogyakarta city government is also a considerable factor. Social impact cause internal and external conflict, while the economic impact of society feels very helpful. Gojek sustainable analysis found that Gojek is not a solution for sustainable urban transportation in the future